Karakteristik dan Prosedur Tafsir Ijmali dan Muqaran - Mirwan Sudarmawan Rifai; Muhammad Irham; Rahmi Damia (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Qur’anic exegesis occupies a strategic position in the development of Islamic scholarship, as it functions to explain the meanings and messages of divine revelation in accordance with the context of the Muslim community. Along with the development of time, Muslim scholars have formulated various methods of interpretation, among which the ijm?l? and muq?ran methods represent two prominent approaches with distinct characteristics and orientations. This study aims to examine comprehensively the characteristics, procedures, strengths, and limitations of the ijm?l? and muq?ran methods of Qur’anic interpretation, as well as their relevance in contemporary Qur’anic studies. The research employs a qualitative approach through library research, analyzing classical and modern exegetical works alongside methodological studies of tafs?r and ?ad?th commentary. The findings indicate that tafs?r ijm?l? is a global, concise, and communicative interpretive method, making it particularly effective for da‘wah and Islamic education among the general public. However, this method is limited in terms of contextual and comparative analysis. In contrast, tafs?r muq?ran emphasizes comparative analysis between similar Qur’anic verses, between verses and relevant ?ad?ths, and among the interpretations of different exegetes, thereby producing a deeper, more critical, and objective understanding, although it requires a higher level of scholarly competence. The application of the muq?ran method in interpreting Qur’an 2:228 concerning the meaning of qur?’ demonstrates divergent opinions among classical legal schools and highlights the tendency of contemporary scholars to prioritize the principles of facilitation (tays?r) and the removal of hardship (raf‘ al-?araj). This study concludes that the ijm?l? and muq?ran methods should not be viewed as dichotomous but rather as complementary approaches. Their integration can generate a comprehensive, contextual, and relevant understanding of the Qur’an that responds to the needs of Muslims in the modern era.